Multiple neural network integration using a binary decision tree to improve the ECG signal recognition accuracy - Tran, Hoai Linh; Pham, Van Nam; Vuong, Hoang Nam (Zielona Góra: Uniwersytet Zielonogórski)
The paper presents a new system for ECG ("ElectroCardioGraphy") signal recognition using different neural classifiers and a binary decision tree to provide one more processing stage to give the final recognition result. As the base classifiers, the three classical neural models, i.e., the MLP ("Multi Layer Perceptron"), modified TSK (Takagi?Sugeno?Kang) and the SVM ("Support Vector Machine"), will be applied.
Keywords: neural classifiers; integration of classifiers; decision trees; arrhythmia recognition; Hermite basis function decomposition